2018
DOI: 10.21767/2471-8173.100042
|View full text |Cite
|
Sign up to set email alerts
|

Is the Interspinous Device (Coflex) Outdated in the Treatment of Lumbar Spinal Stenosis? A Seven-Year Follow-up

Abstract: Background: Coflex, a kind of dynamic interspinous spacer, has been widely used for the treatment of lumbar spinal stenosis in the past a few years. However, controversy remains as to whether dynamic interspinous spacer use is superior to traditional decompression and fusion surgery. High complication, reoperation rate, and costs with poor outcomes were also mentioned in the literature. The aim of the present study is to evaluate whether Coflex implantation following spinal decompression provided better clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, a larger preoperative ROM of the implanted segment indicated that adjacent segments need to compensate more. Previous biomechanical and clinical studies have explained the compensatory loading transfer (33) and increased ROM (34)(35)(36) at adjacent levels after rigid fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a larger preoperative ROM of the implanted segment indicated that adjacent segments need to compensate more. Previous biomechanical and clinical studies have explained the compensatory loading transfer (33) and increased ROM (34)(35)(36) at adjacent levels after rigid fixation.…”
Section: Discussionmentioning
confidence: 99%